2016
DOI: 10.5430/air.v6n1p69
|View full text |Cite
|
Sign up to set email alerts
|

Information-based methods for evaluating the semantics of automatically generated test items

Abstract: Multiple-choice questions are the popular type of test items that are used for testing the knowledge of health-science students in north America and elsewhere. The motivation of this article is to present the recent advances in the automatic item generation (AIG) and to propose a novel unsupervised approach that extends the information-based Compositional Distributional Semantic Model (CDSM) to measure the semantic relatedness among the pool of automatically generated items. We have used operational item bank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Item models with a low CSI average and a high SD will generate items that are highly different from one another, also known as variants (Gierl & Lai, 2013). We used the study by Latifi et al (2017), which found that the item model that generated isomorphs will have a CSI average of over 0.70 and a SD of lower 0.10. While item model that generated variants will have a CSI average of lower 0.70 and an SD of over 0.10.…”
Section: Discussionmentioning
confidence: 99%
“…Item models with a low CSI average and a high SD will generate items that are highly different from one another, also known as variants (Gierl & Lai, 2013). We used the study by Latifi et al (2017), which found that the item model that generated isomorphs will have a CSI average of over 0.70 and a SD of lower 0.10. While item model that generated variants will have a CSI average of lower 0.70 and an SD of over 0.10.…”
Section: Discussionmentioning
confidence: 99%
“…CSI is a text-vector indexing technique which measures the similarity between two vectors of co-occurring text. A distance score is used to compare the similarity of the text (Becker & Kao, 2009; Latifi, Gierl, Wang, Lai, & Wang, 2016). The wording of the key and each option were compared with a root word dictionary.…”
Section: Methodsmentioning
confidence: 99%